Improvements to conventional methods for determining lung cancer areas from CT scan images using ImageJ - software - Edwar Iswardy; Munzir Munzir; Evi Yufita (Universitas Sebelas Maret, 2022)
Early detection of lung cancer will definitely help the patients in treating the illness precisely and as early as possible. One of the methods used to detect lung cancer is through CT scan examination. The images from CT scan will show the cancer area of lung describing the severity of lungs affected by cancer. However, the conventional method is often not accurate. Therefore, this research aims to determine the area of cancer by segmenting the lung organs affected by cancer using Image-J software. The edge detection method was employed to segment an image. The results show that by using the proposed method, the largest cancer area is obtained in the seventh slice with the area of 15.39 cm2 and the smallest cancer area is obtained in the first slice with the area of 1.52 cm2. Whereas by using the convetional method, the largest cancer area is obtained in the fourth slice with the area of 20.57 cm2 and the smallest cancer area is obtained in the teenth slice with the area of 3.52 cm2. The area of lung cancer in each CT Scan slice determined using ImageJ software is more accurate than the conventional method. For that reason, the proposed technique is potential to improve the accuracy of a medical image analysis.